Ground‐dwelling mammal diversity responds positively to productivity and habitat heterogeneity in a fire‐prone region. Issue 9 (21st September 2020) - Swan, Matthew; Christie, Fiona; Steel, Erin; Sitters, Holly; York, Alan; Di Stefano, Julian
Abstract: Environmental heterogeneity has a consistent, positive effect on species diversity globally, principally due to increased niche space in heterogeneous environments. In flammable ecosystems, fire‐mediated heterogeneity (pyrodiversity) is expected to increase species diversity, and the application of diverse fire regimes is a common management goal. We used landscape‐scale sampling units and linear mixed models to determine the response of ground‐dwelling mammal alpha, beta, and gamma diversity to spatial habitat heterogeneity (functional heterogeneity) and three indirect measures of spatial heterogeneity, two pyrodiversity indices based on fire history maps, and another based on mapped vegetation types. In addition, we tested the consistency of species diversity responses across a productivity gradient and examined the extent to which prescribed fire influenced habitat heterogeneity. Beta diversity responded positively to habitat heterogeneity across the productivity gradient, but more strongly at high compared with low productivity. In contrast, alpha and gamma diversity responded positively to productivity, while a weak negative effect of habitat heterogeneity on alpha diversity was also evident. At the scale of our investigation, the productivity gradient across the study area was the most influential driver of species diversity. Spatial heterogeneity within 100‐ha landscapes increased community differentiation among sites (beta diversity), had a weak negative effect on alpha diversity, but had no influence on landscape‐scale species richness (gamma diversity). The occurrence of recent fire had a strong, positive effect on habitat heterogeneity, while the diversity of vegetation types and postfire age classes had a smaller positive influence. Our findings show that prescribed fire can be used to increase landscape‐scale structural heterogeneity, but this will not always result in additional species. Finally, we suggest that using a functional representation of spatial heterogeneity (e.g., the spatial arrangement of habitat structure) as a predictor of species diversity is likely to reveal responses that may otherwise be overlooked. Modern remote‐sensing technologies will aid the development of habitat‐based heterogeneity metrics across large spatial extents.